Gastrointestinal parasites of zoonotic importance observed in the wild, urban, and captive populations of non- human primates in Malaysia - Madinah, Adrus; Ramlah, Zainudin; Mariana, Ahamad; Mohd Azlan Jayasilan, Abdul Gulam Azad; Mohd Tajuddin, Abdullah (John W iley & Sons Ltd, 2018)
Background: A study was undertaken to determine gastrointestinal (GI) parasites commonly found in Malaysia’s non- human primates (NHP) living in three different types of populations (wild, urban, and captive) and the basis of major GI parasites of zoonotic importance. Methods: A total of 308 samples was collected and microscopically screened from the NHP in the wild (n = 163), urban (n = 76), and captive (n = 69) populations. The samples were taken from 12 species of local NHPs. Results: At least, 44 species of GI parasites comprising of protozoans (seven species), nematodes (26 species), cestodes (five species), trematodes (five species), and pentastomida (one species) were detected. There were no significant differences for the overall prevalence and no great differences in GI parasite species among the wild, urban, and captive NHP populations. Conclusion: The most common GI parasite was Ascaris spp. (49.7%), followed by Oesophagostomum spp. (26.9%), and 31 species discovered in this study are of known public health importance.